Presentasi Diri Netizen Dalam Konstruksi Identitas Di Media Sosial Dan Kehidupan Nyata - Nuriyatul Lailiyah (JURNAL ILMU SOSIAL, 2016)
In real life we often took identity as something given. Social media gave users the opportunity to present themselves as they wished. Social media gave chances to people to choose the kind of person they wished to be in social medai. People could then construct their identity the same as or different from their true selves in the real world.This study aimed to identify and understand the self-presentation of social media users in the construction of identity in social media and identity in real life. The study was conducted through the methods of phenomenology and avatar research. Data was gathered by by in-depth interviews and observations in informants social media accounts.The results showed several findings, namely: construction of identity in social media take the positive part of identity in the real world, informants consistently set a certain image in the social media in match to their expectations, social media became a mean of users personal branding. Informants also divided into two categories: first, the group that consistently maintain the image they were trying to build. second, groups that occasionally appeared different from the image they wanted to construct.